Relationship Of Self Determination With Academic Resilience In Facing Lectures - Ramadhani, Rizka Dwi (INDONESIAN NURSING JOURNAL OF EDUCATION AND CLINIC (INJEC), 2022)
Introduction: Self-determination is a method of internal student motivation for reaching their academic goals. Students encounter academic challenges while working toward their goals, which causes them to develop varied levels of resilience.Methods: A cross-sectional method and correlation description were utilized in the research design. Using a proportionate stratified random sampling technique, this study involved 243 students from a state university in Pekanbaru. Self-determination was measured by Basic Psychological Need Satisfaction Scale (BPNS) in General and the Academic Resilience Scale  to measure academic resilience.Results: The results showed that there was a siginificant relationship between academic resilience and self-determination (p = 0,000).Conclusions: Students' levels of self-determination are strongly connected with how resilient they are in the classroom. The level of self-determination displayed by students during lectures is directly correlated with the degree of academic resilience displayed by those students. Researchers encourage students to strengthen their academic resilience and maintain their motivation for success since those that do it would be more motivated to do well in college.